The nonprofit organizational culture guide revealing the hidden truths that impact performance - Teegarden, Paige Hull.; Hinden, Denice Rothman; Sturm, Paul, 1952-; Brinckerhoff, Peter (San Francisco : Jossey-Bass, 2011)
"Part practical guide and part reference, the authors draw upon contemporary research to thoroughly examine and define organizational culture, then explore its implications for nonprofit organizational management. The book guides readers through the process of Revealing Organizational Culture (the ROC), an assessment which helps leaders successfully apply the principles of culture to achieve their organizational goals by analyzing organizational stories. This book is a comprehensive guide for nonprofit managers and leaders, board members, consultants, funders, and others who seek to help nonprofits improve their organizations, service delivery, and ultimately performance in accomplishing their missions."--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nonprofit organizations -- Management; Corporate culture; Performance; Electronic books